2016
DOI: 10.1371/journal.pone.0167420
|View full text |Cite
|
Sign up to set email alerts
|

Substance P Induces HO-1 Expression in RAW 264.7 Cells Promoting Switch towards M2-Like Macrophages

Abstract: Substance P (SP) is a neuropeptide that mediates many physiological as well as inflammatory responses. Recently, SP has been implicated in the resolution of inflammation through induction of M2 macrophages phenotype. The shift between M1-like and M2-like, allowing the resolution of inflammatory processes, also takes place by means of hemeoxygenase-1 (HO-1). HO-1 is induced in response to oxidative stress and inflammatory stimuli and modulates the immune response through macrophages polarisation. SP induces HO-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 49 publications
1
28
0
Order By: Relevance
“…24 Nrf2 is a basic leucine zipper (bZIP) protein that regulates the expression of antioxidative proteins, such as HO-1. 25 To examine the antioxidative and anti-inflammatory effect of carboxyl-Gd 3 N@C 80 , we pretreated Raw 264.7 cells with nanoparticle at 3.5 µ M for 20 h and LPS for another 4 h. Total RNA were isolated, reverse-transcribed to cDNA, and analyzed with real-time PCR. As shown in Figure 3, LPS significantly promoted the mRNA expression of iNOS (** p < 0.01) and TNF- α compared to the control (*** p < 0.001).…”
mentioning
confidence: 99%
“…24 Nrf2 is a basic leucine zipper (bZIP) protein that regulates the expression of antioxidative proteins, such as HO-1. 25 To examine the antioxidative and anti-inflammatory effect of carboxyl-Gd 3 N@C 80 , we pretreated Raw 264.7 cells with nanoparticle at 3.5 µ M for 20 h and LPS for another 4 h. Total RNA were isolated, reverse-transcribed to cDNA, and analyzed with real-time PCR. As shown in Figure 3, LPS significantly promoted the mRNA expression of iNOS (** p < 0.01) and TNF- α compared to the control (*** p < 0.001).…”
mentioning
confidence: 99%
“…Early nonbacterial inflammation may result in damage to injured tissue and accelerate the eventual failure of many medical implants . Macrophages with a spectrum of possible phenotypes play an important role in inflammatory cascade . M1 (classical) and M2 (alternative) activation represent the two extremes of a continuum in a universe of activation states .…”
Section: Resultsmentioning
confidence: 99%
“…Accumulated release of NO in the medium is an indicator of the protein inducible nitric oxide synthase (iNOS), expressed by M1 macrophages. This enzyme could metabolize arginine to NO and citrulline . Figure 10 showed that after being treated with LPS, nitrite production (the stable metabolism of NO) from RAW 264.7 cells was promoted at both 6 and 24 h. When cells were exposed to Dex and LPS, a substantial suppression of NO production was detected.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations